Numerical Analysis of Single Edge Notched Tension Specimen With Fatigue Crack Parameter of Conventional Specimen Using Linear Elastic Fracture Mechanics - Busari, Yusuf Olanrewaju; Abdullah, Shahrum; Manurung, Yupiter H.P.; Shuaib-Babata, Yusuf Lanre (International Journal of Integrated Engineering, 2021)
This paper describes the numerical analysis of planar crack growth in high strength steel API 5L X70 whose crack growth parameter is adopted from experimental compact tension (CT) specimen in previous literature. Apart from the fact that conventional fatigue crack growth specimen has bogus geometry constraints, the Single Edge Notched Tension (SENT) better replicate the crack-tip constraint conditions experienced in structures. Linear elastic fracture mechanics (LEFM) crack orientation is modelled with the finite element method in SENT model considering its geometry functions a/W ratio to determine its crack growth rate based on constant amplitude load. The virtual crack closure technique tool in MSC Marc/Mentat software with adaptive and global remeshing is applied to assess high cycle fatigue crack propagation using the SENT model. The crack growth pattern for the 3-dimensional simulation characteristics is similar with that of the CT Specimen experimental procedure. Furthermore, the results of the crack propagation and the cycle count demonstrated good agreement with bearable discrepancy with maximum percentage difference of about 14.1 % for the HAZ and 6.4% for the weld and parent metal compared to the experimental results from literature.